Discriminating viscous-creep features (rock glaciers) in mountain permafrost from debris-covered glaciers – a commented test at the Gruben and Yerba Loca sites, Swiss Alps and Chilean Andes - W. Haeberli; L. U. Arenson; J. Wee; C. Hauck; N. Mölg (The Cryosphere, 2024)
Viscous-flow features in perennially frozen talus/debris called rock glaciers are being systematically inventoried as part of the global climate-related monitoring of mountain permafrost. In order to avoid duplication and confusion, guidelines were developed by the International Permafrost Association to discriminate between the permafrost-related landform “rock glacier” and the glacier-related landform “debris-covered glacier”. In two regions covered by detailed field measurements, the corresponding data- and physics-based concepts are tested and shown to be adequate. Key physical aspects which cause the striking morphological and dynamic differences between the two phenomena/landforms concern the following: tight mechanical coupling of the surface material to the frozen rock–ice mixture in the case of rock glaciers, contrasting with essential non-coupling of debris to the glaciers they cover; talus-type advancing fronts of rock glaciers exposing fresh debris material from inside the moving frozen bodies, as opposed to massive surface ice exposed by increasingly rare advancing fronts of debris-covered glaciers; and increasing creep rates and continued advance of rock glaciers as convex landforms with structured surfaces versus predominant slowing down and disintegration of debris-covered glaciers as often concave landforms with primarily chaotic surface structure. Where debris-covered surface ice is or has recently been in contact with thermally controlled subsurface ice in permafrost, complex conditions and interactions can develop morphologies beyond simple either–or-type landform classification. In such cases, the remains of buried surface ice mostly tend to be smaller than the lower size limit of “glaciers” as the term is applied in glacier inventories and to be far thinner than the permafrost in which they are embedded.